THERAPEUTIC USES OF IMMUNE SYSTEM: NEW POSSIBILITIES, NEW HOPES - Iqbal, Tehseen (Pakistan Journal of Physiology, 2015)
Our immune system is an amazingly complex system that is ill-defined anatomically but relatively well-defined physiologically. The fact is that we still don’t have a thorough knowledge of this important body system. Our Immune system is capable of defending ourselves against invading pathogens; removing old, worn out or damaged body cells; identifying and destroying the foreign cells; identifying and destroying the abnormal, infected, mutant and cancer cells. The immune system, anatomically, consists of white blood cells (WBCs), tissue cells derived from WBCs, the thymus, the bone marrow, the lymph nodes and the lymph vessels. Antibodies, interferon, and complement system are the chemical weapons and the cytokines are the major communicating chemicals of the immune system. Cytotoxic T Lymphocytes (CTL) in our immune system are the most potent killers of foreign cells. Cytotoxic T lymphocytes (also called T-effecter cells, Teff or TC) and the Natural Killer (NK) Lymphocytes can recognize and destroy the cancer cells. The future of cancer immunotherapy seems to be a promising one because of a number of latest discoveries and new techniques. The reason why cancer immunotherapy is not yet in widespread use is that we still have gaps in our knowledge about the human immune system. Latest studies are examining the possibility to use immunotherapy in conjunction with radiation and chemotherapy to increase the effectiveness of patient responses. Researchers can now reproduce natural body products that can be used as drugs in the treatment of many diseases, including cancer. Some of the modern techniques that are used to achieve this miraculous success are development of monoclonal antibodies, genetic engineering and hybridoma technology.